ANALISIS KESESUAIAN LAHAN PEMUKIMAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI WILAYAH KECAMATAN KOTO TANGAH KOTA PADANG - Panji Musafir Satria; Hary Febrianto; Yulianita Yulianita (Universitas Tamansiswa Padang, 2025)
This study aims to analyze the suitability of residential land using a Geographic Information System (GIS) in Koto Tangah District, Padang City, and to compare it with the Regional Spatial Planning (RTRW). The research method used was descriptive quantitative with spatial analysis techniques through scoring, weighting, and overlay of several parameters, namely slope gradient, rainfall, soil type, land movement, and distance to main roads. The research data were obtained from various secondary sources such as Ina Geoportal, CHIRPS, and PVMBG. The results showed that most areas of Koto Tangah District have moderate to high land suitability levels for residential development, especially in lowland areas with good accessibility. Areas that are less suitable are generally located on steep slopes, prone to land movement, and have high rainfall intensity. The comparison with the RTRW indicates that most residential areas are in accordance with the spatial planning directives, although there are still several areas that require land use control to achieve sustainable development.